On Weighted Approximation by Modified Bernstein Operators for Functions with Singularities (Analysis in Theory and Applications, 2014)
Della Vecchia et al. (see [2]) introduced a kind of modified Bernstein operators which can be used to approximate functions with singularities at endpoints on $[0,1].$ In the present paper, we obtain a kind of pointwise Stechkin-type inequalities for weighted approximation by the modified Bernstein operators.
Keywords: Modified Bernstein operators; weighted approximation; Stechkin inequality.